Insights Into Global Engineering Education After the Birth of Industry 5.0 - Bouezzeddine, Montaha (IntechOpen, 2022)
Insights Into Global Engineering Education After the Birth of Industry 5.0 presents a comprehensive overview of recent developments in the fields of engineering and technology. The book comprises single chapters authored by various researchers and edited by an expert active in the engineering education research area. It provides a thorough overview of the latest research efforts by international authors on engineering education and opens potential new research paths for further novel developments.